Peculiarities of extraction of β-lactoglobuline in protein mineral concentrates at electroactivation of whey - BOLOGA, Mircea; VRABIE, Elvira; PALADII, Irina; ILIASENCO, Olga; STEPURINA, Tatiana; VRABIE, Valeria; POLICARPOV, Albert; SPRINCEAN, Catalina (One Health & Risk Management, 2020)
Introduction. Whey is a by-product and an excellent source of proteins that is rather aggressive due to a large amount of organic substances it contains. The electro-activation of whey applied in the experiments is a wasteless method that allows the va-lorification of all whey components. β-lactoglobulin (β-Lg) makes up 50% of the whey proteins and 12% of the total protein content in milk. Material and methods. The recovery of β-Lg in protein-mineral concentrates (PMC) by electro-activation processing of different types of whey with different initial protein content was investigated in seven configurations. The recovery of protein fractions in the PMCs were analyzed via electrophoresis with sodium dodecyl sulfate (SDS-PAGE) and 15% non-denaturing polyacrylamide gel (PAAG).      Results. Whey electro-fractionation and the obtaining of PMCs with predetermined protein content, namely of β-Lg, were studied on three whey types, processed at different treatment regimens and in seven configurations. The proper management of electroactivation by varying the treatment regimens will allow the electro-fractionation of different types of dairy by-products.Conclusions. The maximum amount of β-Lg recovered in PMCs on electroactivation is  66-71% depending on the processed whey and on the treatment regimens. Obviously, the extraction of β-Lg from initially lower protein content shows a higher recovery degree of β-Lg. The registered temperatures allows formation of PMCs without thermal denaturation.